Students’ Perceptions on the Use of Self-Assessment in Writing Competence - Kadek Fradita Febyone; Dewi, Ni Luh Putu Eka Sulistia; Wahyuni, Luh Gede Eka; Paramartha, Anak Agung Gede Yudha (Universitas Pendidikan Ganesha, 2024)
The use of self-assessment is not effective, this is the result of a lack of guidance or support provided by teachers during self-assessment which is a common reason. Although students carry out their own self-assessment, teachers also play an important role. Teachers need to provide consistent and detailed instructions regarding self-assessment procedures so that students are able to internalize the concepts involved. This study aimed to analyze students perception on the use of self-assessment in their writing competence and to identify the challenges they face. This study uses a survey design with a qualitative approach. 9th grade students as the participants of this study. Questionnaire and interview were used to collect the data. Thematic analysis is a method of analyzing qualitative data to describe and interpret the data interview. The findings show that students have positive perception towards self assessment, which are specifically categorized into four main themes. Firstly, self-assessment is useful for students to improve their writing competence, self-assessment encourages students to developed their quality of writing, self-assessment helps student to achieve their expectation of writing competence, and self-assessment helps students to assess their writing competence. Additionally, the challenges found also categorized into three themes, such as students feel underestimated regarding their writing competence, students feel less objective in assessing their writing competence, and students feel they lack time in assessing their writing competence.